Institutional logics and intra-organisational dynamics: understanding changes in the organisational identity of a UK law firm - Hartwell, Kathryn Louise (2017)
This research explores the relationship between institutional field level change and organisational change. More specifically, the focus of this study centres on the influence which a transition between institutional logics has on an organisation’s identity. Via an in-depth case study of a medium-sized, international commercial law firm, findings suggest that institutional field level change is manifested at the organisational level through the use of signs. Contrary to existing literature which focuses on the presence of a singular organisational strategy as a response to external field level change, this study indicates that multiple organisational strategies can co-exist, as evidenced through the use of signs. To this end, a semiotic analysis of empirical data suggests that evidence of decoupling, hybridisation and substitution can all be found co-existing within one organisation. Moreover, findings indicate that an organisation’s selection of organisational strategy is dependent on the relative proximity of a given sign from the external boundary of the organisation. Significantly, such findings are especially insightful in indicating how organisations make sense of and respond to institutional field level changes in real-time.